Análisis del apremio personal para el alimentante que deba pensiones alimenticias y la vulneración del derecho constitucional a la libertad - Paredes Henríquez, María Elena (2021)
The right for minors to be guaranteed their livelihood through a pension for a good living and the right of every human being to freedom and not to be deprived of it by duty of food pension is the subject of this work, the right of minors and the right to freedom constitute guarantees in the Constitution of Ecuador , but there is an exception in the same constitution that expressly states "That no person may be deprived of his liberty for debts, costs, fines, taxes, or other obligations, except for alimony." Both rights apart from being guaranteed in the Ecuadorian constitution, are in international conventions as in the case of children is the Convention on the Rights of Children in it emphasizes the principle of the Higher Interest of the Child that serves as a tool to implement their rights through laws conducive to their wellbeing in the domestic legislation of each country.........